Structure of the Main Central Thrust zone and extrusion of the High Himalayan deep crustal wedge, Kishtwar-Zanskar Himalaya - Stephenson, B; Searle, M; Waters, D; Rex, D (2001)
The Main Central Thrust is a crustal-scale ductile shear zone between 1.5 and 3 km wide which places the Oligocene-Miocene metamorphic rocks of the High Himalayan zone south or SW over the unmetamorphosed or weakly metamorphosed rocks of the Lesser Himalaya. The high strain zone of the Main Central Thrust is coincident with an inverted metamorphic field gradient from biotite to kyanite grade over a structural thickness of 1500 m. Kyanite-grade rocks metamorphosed at 9.5-10 kbar were exhumed from depths of 33-37 km along the Main Central Thrust hanging wall and emplaced over Lesser Himalayan rocks never buried deeper than 10-12 km. Exhumation of the deepest buried kyanite-grade rocks occurred along the zone. Above the Main Central Thrust zone approximately 45 km width (28 km structural thickness) of the High Himalaya exposes sillimanite-grade gneisses, migmatites and 19.5-21.5 Ma old leucogranites formed at pressures between 4.5 and 7 kbar and depths of 16-25 km. A NE-dipping normal fault ductile shear zone at the top of the slab (Zanskar Shear Zone) shows condensed but right way-up isograds from sillimanite to chlorite grade over 2-400 metres structural thickness. 40Ar/ 39Ar geochronology shows that most of the High Himalayan slab had cooled below 350°C by 16 Ma supporting models linking the two bounding faults of the High Himalaya both kinematically and temporally. There is no evidence of melting along the Main Central Thrust zone and the Himalayan leucogranites were generated 10-30 km structurally above the Main Central Thrust. Frictional heating along the Main Central Thrust could not therefore have played any role in generating the leucogranites. Thus far, there is little evidence for late Miocene reactivation along the Main Central Thrust, as seen elsewhere along the Main Central Thrust in Nepal.